BRANDING PERGURUAN TINGGI SWASTA (STUDI KASUS STRATEGI MARKETING PUBLIC RELATION UNIVERSITAS KRISTEN INDONESIA MALUKU). - LATUHERU, RIDO DOMINGGUS (JURNAL BADATI, 2019)
Marketing and branding are two things that are interconnected with each other. Marketing talks about a product idea, about the distribution system and sales chain, the size of the gross margin, the promotional budget and some of the profits that producers can achieve. Formulation of the problem Based on the description on the background and identification of the problem, then the problem of this research can be formulated is to find out How is UKIM's public relations marketing strategy in branding? Based on the problem above, the research objectives achieved are: (1). Knowing UKIM's Public Relations Marketing Strategy in Branding? (2). What is the Public Response to the Public Relations Marketing Strategy in Branding? The benefits of this study are expected to be useful as (1). Contribution of ideas and input and helped UKIM in formulating the Public Relations Marketing Strategy in Branding. (2). Scientific input for the development of the UKIM Research Institute, particularly in the field of Communication Studies